Pengaruh Tawakal terhadap Pencarian Rezeki sebagai Guru - Muhammad Syahrul Munir (Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2018)
Profession of  teacher do not make as a basical subject of  livelihood.  But must be consciously that teach as a obligation to channel of  knowledge.  Because of that,  this papper research have a tawakal implanted in a teacher attitude? Which their attitude dominated by sincerity.  This research used method of qualitative research with psychology approach.  This research found that tawakal still dominate of teacher attitude,  although sometime there are feeling unsincerity and unsatisfaction with their wage.